Re-layout beverage and dry goods set-up area at pt. Karunia food - Ondania Keloko, Lea Lehelia; Nizar, Adirizal (The Indonesian Journal of Business Administration, 2019)
Abstract - PT Karunia Food is a company which engages in in-flight catering to support catering and logistic supplies for a national airline. For the logistic supplies, PT Karunia Food must prepare various kinds of inventories, such as monouse, multiuse, dry goods, and beverages. The logistics that have been arranged to trolleys or containers will be transferred to the assembly line and will be uplifted to the aircraft. The business process will be continued after the aircraft landing because the multiuse inventory will be offloaded from the aircraft and transferred back to each setup area. The absence of recording the items that offload from the aircraft caused a lot of loss and breakage items which generate an increase in inventory cost. To reduce it, PT Karunia Food will implement barcoding system to control the inventory items that the company have. With this system, the items that will be uplifted and offload after aircraft landed could be counted, so the items that already consumed can be calculated properly for the procurement planning. For the implementation of barcoding system, PT Karunia Food implements first on beverage and dry goods setup area. In this area, there are six setup processes of items needed for the aircraft, which are beverages, dry goods, mineral water, amenities, paper cups, and miscellaneous. But, for the implementation, there is a problem with the insufficiency of the area to do the barcoding process, so the barcoding system cannot be implemented. The research methodology used in this research is using qualitative method through the author’s observation and interview to find the root cause of does not have space to implement barcoding system. The interviewee are the head, administration officer, and staff that involves in the setup area. After interview, the author analyzes using the fishbone diagram and found that there are four root causes that make the company does not have enough space to implement barcoding system in the beverage and dry goods setup area, which are unclear flow process, does not have SOP (Standard Operating Procedure), unclear distribution of task, and unclear layout. The proposed solutions are making the new flow processes, making SOP, making clear job description, and making a new layout. Flow process analysis is being used to make the new flow processes. The first solution that the company has to applied is making the new flow processes first to make a process which have a proper flow which will be used for next solution, which is making a new layout. After those two solutions are done, the next solution is making SOP for each process and making a clear job description for the manpower. Keywords: Setup Area, Flow Process, Re-Layout, Fishbone Diagram